Violencia y muerte en el mundo popular: reflexiones en torno al simbolismo de las animas - Ricardo Salas Astrain (Estudios sobre las Culturas Contemporáneas)
Here is exposed a reflection arround the symbolism (practices, rituals, bealivings, myths) that build up upun "animitas" somo inhabitants of peasant zones and popular wards of Santiago de Chile. This text analyses the symbolic relation between the death cult and violence. It descrives the typology/topography of this phenomenon, the myth and unjust bealivings that sorround the victim`s death.